Metabolome alterations in pediatric metabolically unhealthy obesity are primarily linked to abnormal glucose homeostasis - Daniel Zhi Wei Ng; Yu Hao Shie; Sandheep Ransilu Piyasanka; Dorinda Yan Qin Kioh; Andrew Anjian Sng; Bee Wah Lee; Yung Seng Lee; Eric Chun Yong Chan; Delicia Shu Qin Ooi (Scientific Reports)
Abstract The mechanisms underlying metabolically healthy obesity (MHO) in pediatrics remain poorly understood. This study aims to evaluate the plasma metabolome of MHO versus metabolically unhealthy obesity (MUO) in Asian children and adolescents, to identify key metabolic drivers that undergird the MUO phenotype. MHO and MUO were defined by the absence or presence of metabolic syndrome criteria, respectively. We conducted untargeted metabolomics analysis on plasma samples from children and adolescents without obesity (n = 24), with MHO (n = 65) and with MUO (n = 222). Multivariate data analyses identified key metabolites differentiating the groups. Logistic regression assessed metabolite associations with metabolic conditions, while Spearman’s correlation evaluated their links to cardiometabolic parameters. Metabolites such as plasma fatty acids, amino acids and 1,5-anhydroglucitol differentiated MHO from MUO, correlating significantly with parameters of glucose homeostasis. Plasma branched-chain amino acids and 3-hydroxyisobutyric acid were elevated while 1,5-anhydroglucitol was reduced in pediatrics with obesity and abnormal glucose tolerance compared to those with obesity and normal glucose tolerance. Our study revealed distinct metabolome alterations between MHO and MUO in Asian children and adolescents. Notably, we identified that these metabolomic differences between MHO and MUO are primarily linked to abnormal glucose homeostasis, highlighting potential metabolic targets for improving health outcomes in pediatric obesity.